Lithuanian emigrants book publishing in Western Europe in 1945-1952 like first etape of post-war Lithuanian emigrants book publishing - Misiūnas, Remigijus (Knygotyra, 1998)
Knowledge of Lithuanians emigrants’ book publishing in Western Europe in 1945–1952 is very actual for post-war Lithuanian emigrants’ book publishing research, because base for latest publishing was lay in this time. Needs of education system, fiction and religious literature stimulated publishing in first post-war year. Needs of fiction, religious literature and book in foreign language stimulated publishing in latest year. Circle of publishers was formed in Western Europe in 1945–1952. Most of private publishing houses, who worked there, continues their activity in USA in latest year („Patria“, „Sudavija“, „Gabija“ and other). Publishing houses, who work in book club basic („Nida“ and other) continue traduce of joint-stock publishing houses. Traduce of social organisation and institution publishing houses also didn’t disappear in latest year. Lithuanians also publishing their books in foreigners’ publishing houses all time. Lithuanian emigrants periodical issues („Keleivis“, „Naujienos“ and other), party (LSDP), political (VLIK and other), social (Lithuanian World Society, scouts and other), international (Lithuanian Red Cross and other) and professional (Lithuanian jurist, Lithuanian sailor and other) organisation and institution, education institution, confession institution, separately persons and anonymous publishers work in first post-war and in latest year. Publishers printing there books in foreigners’ printing houses in first post-war year. Lithuanian began created own publishing base since 1949 („Nida“ in Gr. Britain, V. Vijėikis, M. Morkūnas printing house and other in USA). Book polygraph culture level wasn’t had in post-war year. Later publishers try to keep or raise him. Emigrants’ book repertoire began formatted in Western Europe in 1945–1952. Mass-agitation literature publishing was big in first post-war and in latest year in typology aspect, science literature amount began grown after 1952. Humanitarian sciences and fiction literature publishing were big in post-war and in latest year in thematic aspect. Emigrant book was various in language aspect since post-war year. Circle of authors formatted in Western Europe. Book spread was one of biggest publishers’ problem. Practise of spread throughout spreaders was used since post-war year in Western Europe. Periodical issues, book and publishing houses’ catalogues was used as book trade information means all time. Emigrants’ book demands fall down, who began since 1948, became stability, but push, whom emigrants publishing receive in Western Europe, was so strength, that publishing, even weakening, survive vitality some decade.